Correlation Between Physical Activity And Screen Time With Sleep Duration: A Cohort Study Among Pre to Elementary School-aged Children Before, During, And After The Covid-19 Pandemic - Rhanindra Aviana Yumna Shafira; Lukman Fauzi (Journal of Health Education, 2025)
Background: The COVID-19 pandemic has significantly altered children's daily routines, particularly increasing screen time, decreasing physical activity, and changing sleep duration, which may impact their physical and mental health. It is important to know how changes in physical activity and screen time can affect children's sleep duration before, during and after the COVID-19 pandemic. Methods: This study used a quantitative analytical observational cohort study method with 240 child samples aged 6–12 years in Semarang City. The sampling technique used simple random sampling. The research instrument used the SMALLQ® questionnaire. Data analysis techniques used normality tests, Spearman-Rank tests to determine correlations, and Kruskal-Wallis tests to compare data. Results: The correlation between screen time and sleep duration was not statistically significant (p>0.05), while physical activity showed a significant positive correlation with sleep duration (r = 0.253 on weekdays, r = 0.21 weekly, p<0.05). Significant differences were found in screen time, physical activity, and sleep duration across the three periods (p<0.001), with increased screen time and decreased physical activity and sleep duration persisting post-pandemic.  Conclusions: The pandemic led to lasting increases in screen time and decreases in physical activity and sleep duration among children. Promoting healthier routines is essential to mitigate these impacts in the new normal era.